(untitled) (Rivista di Studi e Ricerche sulla criminalità organizzata, 2015)
Proprety investigation, financial power, fiscal paradise. This is the new language that Giovanni Falcone brought in the struggle against the mafia, moving from the prosecution against Rosario Spatola, entrepreneur linked to Bonatate-Inzerillo clan, in early eighties. In this way he started his revolution in the concepts and in the investigative methods